2018
DOI: 10.1093/sf/soy072
|View full text |Cite|
|
Sign up to set email alerts
|

Punishment and Inequality at an Early Age: Exclusionary Discipline in Elementary School

Abstract: We advance current knowledge of school punishment by examining (1) the prevalence of exclusionary discipline in elementary school, (2) racial disparities in exclusionary discipline in elementary school, and (3) the association between exclusionary discipline and aggressive behavior in elementary school. Using child and parent reports from the Fragile Families Study, we estimate that more than 1 in 10 children born 1998-2000 in large US cities were suspended or expelled by age nine, when most were in third grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 42 publications
1
37
0
1
Order By: Relevance
“…Reform efforts have led to recent declines in some states (Loveless, ), but overall rates are still high, particularly for disadvantaged and racial minority students, not because juvenile crime rates are high but because suspension is often in response to minor misbehavior like classroom disruptions and attendance problems (Kupchik, ; Morris & Perry, ; Skiba et al., ). This is problematic because in a growing body of research, scholars have suggested that suspension may be harmful for child and adolescent development (Cuellar & Markowitz, ; Jacobsen, Pace, & Ramirez, ; Mittleman, ; Morris & Perry, ).…”
Section: Introductionmentioning
confidence: 99%
“…Reform efforts have led to recent declines in some states (Loveless, ), but overall rates are still high, particularly for disadvantaged and racial minority students, not because juvenile crime rates are high but because suspension is often in response to minor misbehavior like classroom disruptions and attendance problems (Kupchik, ; Morris & Perry, ; Skiba et al., ). This is problematic because in a growing body of research, scholars have suggested that suspension may be harmful for child and adolescent development (Cuellar & Markowitz, ; Jacobsen, Pace, & Ramirez, ; Mittleman, ; Morris & Perry, ).…”
Section: Introductionmentioning
confidence: 99%
“…This association is troubling given the large racial disproportionality in both incarceration and school discipline. Black children are at greater risk than Whites or Hispanics of having a father incarcerated (Sykes and Pettit 2014); they are also more likely to be suspended or expelled in elementary school (Jacobsen et al forthcoming). Thus, it is important to consider potential implications of these findings for childhood inequality.…”
Section: Discussionmentioning
confidence: 99%
“…By age 9, about 11 percent of children born in urban areas have been suspended or expelled. For Black children, this jumps to 40 percent of boys and 15 percent of girls, compared to 8 percent and 2 percent for their White or other-race counterparts (Jacobsen et al forthcoming).…”
Section: Suspension Expulsion and The School-to-prison Pipelinementioning
confidence: 99%
See 2 more Smart Citations